2022
DOI: 10.3390/healthcare11010045
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions for Prevention and Management of Diet-Linked Non-Communicable Diseases among Adults in Arab Countries

Abstract: The increased incidences of diet-related non-communicable diseases (NCDs) such as diabetes, obesity, and cardiovascular diseases among adults are becoming the chief public health concern in most Arab countries. Economic expansion has contributed to a nutrition shift from a traditional seasonal diet to Westernized eating habits coupled with a sedentary lifestyle. Despite the rising concern for NCD mortality, public health policies are inadequately addressed. This narrative review aims to discuss the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
(427 reference statements)
0
3
0
Order By: Relevance
“…Many studies reported that among the Ara-bic population, especially in Arabic women, there are sociocultural barriers to a healthy lifestyle [109,110]. To be effective, these programs should be modified according to cultural and religious practices [111].…”
Section: Arabic Middle Eastern Dietmentioning
confidence: 99%
“…Many studies reported that among the Ara-bic population, especially in Arabic women, there are sociocultural barriers to a healthy lifestyle [109,110]. To be effective, these programs should be modified according to cultural and religious practices [111].…”
Section: Arabic Middle Eastern Dietmentioning
confidence: 99%
“…These diseases, such as obesity, diabetes, hypertension, cardiovascular diseases, and metabolic disorders, pose a major threat. 1 According to the World Health Statistics 2022 by World Health Organization, NCDs kill 41 million people annually, equivalent to 74% of all deaths globally, with 17 million people dying from an NCD before the age of 70 each year. Moreover, 86% of these premature deaths occur in low-and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high consumptions of white bread and red meat/potatoes were associated with central and global adiposity in adults, respectively [ 17 ]. In addition to the risk of obesity, dietary habits seem to be associated with sedentary behavior in adults [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%